Changes in American Economic Policy in the 1980s: Watershed or Pendulum Swing? - Taylor, John B. (Journal of Economic Literature, 1995)
ECONOMIC POLICY in the 1980s may eventually become the most studied and hotly debated of any in United States history, even including the 1930s. Popular writings about the 1980s economy already abound in hundreds of op-ed pieces, columns, editorials, and books. However, polarization rather than consensus seems to characterize most of these popular writings as witnessed by such contrasting books as Robert Bartley's The Seven Fat Years (1988) with its praise for the policies of the and Paul Krugman's Peddling Prosperity (1994) which finds little if any good that came from them. In fact, most writers have been in one of two camps, either filled with mockery and scorn for the greed decade of the 1980s and the economic policies which define it, or filled with unwavering admiration for the polices of the 1980s which saved America from the ruin caused by the malaise decade in the 1970s. For many there appears to be no more consensus about these policies than at the time they were put into place. Most of the writers on either side of the debate seem to be talking past each other. The 823 page National Bureau of Economic Research Conference volume, American Economic Policy in the 1980s, edited and partly written by Martin Feldstein takes a different approach. It brings together in a single volume a total of 39 economists and policy makers to analyze, discuss, critique, and rebut each others views of U.S. economic policy in the 1980s. What emerges is a thorough and fascinating survey of facts and ideas from this important period in U.S. history. The book deserves to be studied carefully by anyone with a serious interest in economic policy, much like an earlier National Bureau of Economic Research volume-Milton Friedman and Anna Schwartz's A Monetary History of the United States, 1867-1960-it is essential for those interested in earlier periods in the history of U.S. economic policy.